Outcomes of Modified FOLFOX-6 as First Line Treatment in Patients with Advanced Gastric Cancer in a Single Institution; Retrospective Analysis - Lee, Han Hong; Hur, Hoon; Kim, Soo Hong; Park, Ae Ryung; Kim, Wook; Jeon, Hae Myung (Cancer research and treatment, 2010)
Treatment options for patients with advanced gastric cancer remain limited. Few studies have investigated the efficacy and tolerability of the combination regimen of oxaliplatin and 5-fluorouracil with leucovorin for patients with advanced gastric cancer. The goal of this study was to examine the efficacy and toxicity of a modified FOLFOX-6 (mFOLFOX-6) regimen as a first-line chemotherapy regimen for patients with advanced gastric cancer. From March, 2006, to December, 2007, 82 patients with advanced gastric cancer received 100 mg/m² oxaliplatin and 100 mg/m² leucovorin on the first day of treatment, followed by 2,400 mg/m² of 5-fluorouracil on the first and second days of treatment every 2 weeks as a first-line treatment. The median age of the enrolled patients was 62 years (range; 30~75). Out of 82 patients, 34 cases (41.5%) were recurrent cases after curative resection, and the other 48 cases were unresectable or non-curative resectable cases. Their response was evaluated every 6 weeks. The overall response rate was 40.2%, with 2 (2.4%) complete response and 31 (37.8%) partial responses. The median time to progression (TTP) and overall survival (OS) time were 6.0 months (95% confidence interval [CI]: 4.69~7.31) and 13.0 months (7.99~18.0), respectively. The grade 3~4 hematologic toxicities observed included neutropenia (34.1%), thrombocytopenia (7.3%), and anemia (1.2%). The gastrointestinal toxicities observed included grade 3~4 nausea (9.8%) and vomiting (7.3%). Six patients (7.3%) experienced grade 3 neuropathy. No treatment-related deaths were recorded. The modified FOLFOX-6 regimen is effective and well tolerated as a first-line chemotherapy regimen for patients with advanced gastric cancer.